2011
DOI: 10.1371/journal.pone.0019601
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking of Mutation Diagnostics in Clinical Lung Cancer Specimens

Abstract: Treatment of EGFR-mutant non-small cell lung cancer patients with the tyrosine kinase inhibitors erlotinib or gefitinib results in high response rates and prolonged progression-free survival. Despite the development of sensitive mutation detection approaches, a thorough validation of these in a clinical setting has so far been lacking. We performed, in a clinical setting, a systematic validation of dideoxy ‘Sanger’ sequencing and pyrosequencing against massively parallel sequencing as one of the most sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 33 publications
2
70
1
1
Order By: Relevance
“…Additionally, next-generation sequencing methods to compare and validate the results of the EGFR mutation testing by pyrosequencing were not used. However, recent studies have shown that pyrosequencing has the ability to detect EGFR mutations at a low ratio of mutant to wild-type alleles and thus provides high analytical sensitivity for identifying EGFR mutations (32,33). The systematic review is limited in several ways.…”
Section: Distribution Of Mutations In the Egfr Kinase Domain Categorimentioning
confidence: 99%
“…Additionally, next-generation sequencing methods to compare and validate the results of the EGFR mutation testing by pyrosequencing were not used. However, recent studies have shown that pyrosequencing has the ability to detect EGFR mutations at a low ratio of mutant to wild-type alleles and thus provides high analytical sensitivity for identifying EGFR mutations (32,33). The systematic review is limited in several ways.…”
Section: Distribution Of Mutations In the Egfr Kinase Domain Categorimentioning
confidence: 99%
“…Cellular mechanisms of de novo and acquired resistance to EGFR TKI therapy in NSCLC include various molecular abnormalities in tumor cells such as constitutive activation of transducers located downstream of EGFR, overexpression of other tyrosine kinase receptors, or in particular secondary EGFR mutations. Among patients exhibiting acquired resistance, a secondary EGFR exon 20 mutation (T790M) occurs in about 50% of cases and an amplification of MET has been detected in up to 20% of EGFR TKI-resistant tumors [48][49][50][51][52][53][54][55]. Minor clones with the T790M mutation have been identified in Table 1: Currently utilized predictive molecular biomarkers, which may also be used for tumor monitoring in liquid biopsies.…”
Section: Clinical Application Of Ctdna Diagnosticsmentioning
confidence: 99%
“…Choosing higher sensitivity methods may reveal more primary lung tumors carrying the resistance mutation in addition to the classic sensitizing EGFR mutation. Recent studies have shown that alternate methods reveal T790M mutations in up to 79% of EGFR-mutant primary NSCLC tumors [54,55,57,58]. Although, applying more sensitive detection methods such as NGS, dPCR or Beaming technology will provide more insight into the molecular mechanisms of tumor development and tumor progression, heterogeneity is one reason treatment relevant mutations such as T790M are missed at initial diagnosis.…”
Section: Tumor Type Genementioning
confidence: 99%
“…Pyrosequencing was performed on a 70 Â 75 mm picotiter plate using a gasket with distinct compartments for physical separation of the samples. The picotiter plate was inserted in the flow cell and subjected to pyrosequencing on the Genome Sequencer FLX 454 instrument (Roche, Branford, CT, www.roche.com), as described previously [28]. For each deoxynucleotide triphosphate flow, a single image was captured by a charge-coupled device camera on the sequencer.…”
Section: Ngs Of Mtdnamentioning
confidence: 99%